The Impact of Silymarin on Inflammation and Oxidative Stress: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Mahdi Vajdi; Shaghayegh Adeli; Arash Karimi; Vahid Asghariazar; Arezoo Moini Jazani; Ramin Nasimidoost Azgomi (International Journal of Clinical Practice)
Numerous studies have investigated into the antioxidant and anti-inflammatory properties of silymarin, as well as its ability to reduce reactive oxygen species and inflammation biomarkers. The effect of silymarin on inflammation and oxidative stress was investigated using the keywords “milk thistle” OR “Silybum marianum” OR “Silybum” OR “silymarin” OR “Silibinin” AND “MDA” OR “Malondialdehyde” OR “TAC” OR “total antioxidant capacity” OR “IL-10” OR “Interleukin-10” OR “IL-6” OR “Interleukin-6” OR “TNF-α” OR “tumor necrosis factor alpha” on the Web of Science, Scopus, Embase, PubMed, and Cochrane Library, up until March 2023. Data were combined using a random-effects model, and the weighted/standardized mean differences (WMDs/SMDs) with a 95% confidence interval (CI) were used as the overall effect size. Our meta-analysis indicated that silymarin supplementation resulted in a significant decrease in levels of C-reactive protein (CRP) (WMD: −3.39 mg/L, 95% CI: −5.99, −0.79, p=0.01) and malondialdehyde (MDA) (SMD: −1.69, 95% CI: −2.62, −0.76, p<0.001). Furthermore, silymarin significantly increases IL-10 (WMD: 2.03 pg/mL; 95% CI: 1.04, 3.01, p<0.001), superoxide dismutase (SOD) (SMD: 3.39, 95% CI: 1.42, 5.37, p=0.001), and glutathione peroxidase (GPx) (SMD: 1.94; 95% CI, 0.89 to 2.99; p<0.001) level. However, silymarin supplementation did not have significant effects on TAC (SMD: 2.91; 95% CI: −0.30, 6.11, p=0.076) and IL-6 (WMD: −0.70 pg/mL; 95% CI: −1.42, 0.02, p<0.056) level. Silymarin supplementation may significantly improve oxidative stress and inflammation in adults by decreasing CRP and MDA and increasing IL-10, SOD, and GPx. However, additional studies with longer study periods are required to ascertain the long-term effects of silymarin on oxidative stress and chronic inflammation.